Racial Disparities in the Utilization of Lateral Ankle Ligament Reconstruction for Chronic Ankle Instability in the United States - Britanny Hamama BS; Myra Chao BA; Rishin J. Kadakia MD; Jason T. Bariteau MD; Michelle Coleman MD, PhD (Foot & Ankle Orthopaedics, 2023)
Category: Ankle; Other Introduction/Purpose: Chronic ankle instability (CAI) is a common diagnosis among people with previous ankle injuries. Once conservative treatment is exhausted, lateral ankle ligament reconstruction (LALR) is the gold standard surgical treatment for CAI. Previous studies have reported on the impact of race on access to orthopedic procedures in the United States. However, there are few studies evaluating racial disparities in elective foot and ankle surgeries, including LALR. Recognizing and addressing disparities in the access of health resources are imperative in combating systemic care rationing. Thus, our study aims to investigate racial disparities including utilization and perioperative metrics of lateral ankle ligament reconstruction. Methods: A retrospective study was performed using the National Surgical Quality Improvement Program (NSQIP) database. Patients that utilized the Current Procedural Terminology (CPT) code 27698 corresponding to LALR from 2011 to 2020 were included. 61% of these patients had available race/ethnicity data and were included. Designations of race and ethnicity were standardized as White non-Hispanic (WNH), Black non-Hispanic (BNH), Hispanic, Asian American and Pacific Islander (AAPI), and Other. Race/ethnicity stratifications of NSQIP patients were compared to 2010 and 2020 census data from the United States (US) Census Bureau. 30-day postoperative complications and length of hospital stay were also compared between WNH and all other patients combined. Independent T-tests, Chi-squared, and Fisher's exact tests were performed to compare differences including age, gender, and post-operative complications at an α = 0.05. Results: Overall, 1295 patients were included in the study. There were 3.3 times more WNH patients than all other groups who underwent LALR during the study period. This utilization exceeds what would be expected based on population statistics (1.9 times more WNH in the population in 2010 and 1.3 times more WNH in 2020). WNH patients were older with a mean age of 38 years, compared to 36 years for BNH patients (p < 0.05). Amongst the WNH patients, 17.4% smoked which was significantly more than other race/ethnicities. (p=0.012). There were no differences in overall 30-day complication rate or individual types of complications based on race and ethnicity. There were also no significant differences in total length of hospital stay. Conclusion: Our study found that there was increased utilization of LALR amongst White non-Hispanics compared to all other racial/ethnic groups. These numbers do not mimic the current population trends based on the national census data. Despite this discrepancy, no differences in postoperative complications and length of stay based on race and ethnicity were found. These results suggest that there may be systemic barriers for patients to undergo care for LALR and that further research needs to be conducted on racial disparities within orthopedics.